A rare occurrence of psoas abscess with uterine didelphys and renal agenesis: A case report. (September 2021) - Mandal, Sujit Kumar; Shikhrakar, Shreeja; Regmi, Binit Upadhaya; Bam, Shiba
Abstract: Introduction: Mullerian duct anomaly such as uterine didelphys is a rare congenital anomaly of female genitourinary tract presenting with dysmenorrhea, hematocolpus, and subfertility in adolescent females. It is commonly associated with wolffian duct anomaly like renal agenesis. Here we present a rare association of psoas abscess with uterine didelphys and renal agenesis in a 21-year-old unmarried female. Case presentation: We report a case of 21-year-old female presenting with right hip pain, recurrent genital infections and dysmenorrhea. Her labs suggested infectious etiology whereas radiological investigation revealed right psoas abscess. In addition, she was found to have uterine didelphys with pyometra, right adnexal mass, and right renal agenesis. Clinical discussion: Uterine didelphys commonly present with dysmenorrhea and hematocolpos along with various non-specific symptoms. Patients can develop psoas abscess secondary to uterine didelphys, but uterine didelphys presenting with psoas abscess is fairly rare. Psoas abscess on itself is a difficult condition to diagnose, more so when associated with rare uterine anomalies. Conclusion: This case highlights the possibility of psoas abscess as a primary presentation of Mullerian duct anomaly. Further, a differential of uterine didelphys should be considered in every reproductive age female presenting with recurrent pelvic infection. Highlights: When a reproductive-age women presents with recurrent pelvic infections, a differential of Mullerian duct anomalies should always be sought out despite the absence of its classical symptoms. Uterine didelphys can also present with rectal, abdominal, or hip pain due abscess formation in related organs and surrounding communicating structures. Our case is an example of atypical presentation of uterine didelphys where the patient presented with psoas abscess which is rare in this entity.